2006
DOI: 10.12681/mms.168
|View full text |Cite
|
Sign up to set email alerts
|

Factors controlling marine fouling in some Alexandria Harbours, Egypt

Abstract: The present work aims to relate the settlement of marine fouling organisms in three different harbours in Alexandria city which present a wide range of ecological/environmental variations. Theses are the Abu Qir, Eastern and El-Dekheila harbours. Monthly samples of marine fouling were collected from the three harbours by using white roughened polystyrene test panels (12.5x12.5 cm), as well as physicochemical, chemical and other biological data. Results were treated with multivariate statistical analysis (PCA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…This indicates higher species richness (RAMADAN et al, 2006b) including more bryozoan species than the other harbours.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This indicates higher species richness (RAMADAN et al, 2006b) including more bryozoan species than the other harbours.…”
Section: Discussionmentioning
confidence: 93%
“…This is mainly correlated with the degree of disturbance at each harbour. RAMADAN et al (2006b) studied the factors controlling the marine fouling at the three harbours and they indicated that diversity indices are related to degrees of eutrophication and/or industrial pollution at each harbour.…”
Section: Discussionmentioning
confidence: 99%
“…Abo Quir Harbor is affected by three continental discharges; they are; boughaz El-Maadia opening, the tapia pumping station and the opening of Rashid Nile branch [30]. In the present study Cu level for the three locations is lower than the Critirion Maximum Concentration (CMC) level for copper which is 4.8 µg/L and the Critirion Continous Concentration (CCC) level which is 3.1 µg/L stated by United State Enviromental Protection Agency [31].…”
Section: Resultsmentioning
confidence: 99%
“…The results of current study were evidenced by the fact that, Abo-Qir station in Alexandria was polluted by the disposal of effluents of both sewage and industrial activities. Ramadan et al [67] found that Abo Qir station was affected by three discharges as Boughaz El-Maadia opening, Tapia pumping station and the opening of Rashid Nile branch. The elevation of Cu level in Abo Qir seawater shown in the current study might be due to leaching of Cu from ships antifouling paints.…”
Section: Discussionmentioning
confidence: 99%